2008
DOI: 10.2119/2008-00081.thompson
|View full text |Cite
|
Sign up to set email alerts
|

Acute, Muscle-Type Specific Insulin Resistance Following Injury

Abstract: Acute insulin resistance can develop following critical illness and severe injury, and the mortality of critically ill patients can be reduced by intensive insulin therapy. Thus, compensating for the insulin resistance in the clinical care setting is important. However, the molecular mechanisms that lead to the development of acute injury/infection-associated insulin resistance are unknown, and the development of acute insulin resistance is much less studied than chronic disease-associated insulin resistance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 50 publications
3
41
0
Order By: Relevance
“…In ICU patients [44], insulin resistance is generally present and associated with deleterious outcomes [45,46]. Animal models have documented the development of insulin signaling defects in muscle, leading to insulin resistance within muscle [47,48]. In humans, muscle is insulin resistant and can respond to intensive insulin therapy [49].…”
Section: Insulin Resistance Has Negative Implications On Muscle Massmentioning
confidence: 99%
“…In ICU patients [44], insulin resistance is generally present and associated with deleterious outcomes [45,46]. Animal models have documented the development of insulin signaling defects in muscle, leading to insulin resistance within muscle [47,48]. In humans, muscle is insulin resistant and can respond to intensive insulin therapy [49].…”
Section: Insulin Resistance Has Negative Implications On Muscle Massmentioning
confidence: 99%
“…These observations suggest that Drosophila could be a useful model not only for studying aging but also obesity. Nevertheless, they do not clearly indicate whether the increase of triglycerides is attributed to insulin resistance, which is not only associated with obesity (76,77) but also with trauma.…”
Section: Discussionmentioning
confidence: 94%
“…Insulin resistance has been suggested to develop following critical illness and severe injury (76). Whether IMCL is an instigator or a marker of insulin resistance is currently a topic of debate (81).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that hepatic insulin resistance occurs in rats 90 min following trauma and hemorrhage (1012; 14; 28). The rats were injected with GdCl 3 and 48 hours post-injection, surgical trauma and hemorrhage for 90 min was performed.…”
Section: Resultsmentioning
confidence: 99%